Experimental Study on a Self-Centering Earthquake-Resistant Masonry Pier with a Structural Concrete Column. (25th May 2017) - Niu, Lijun; Zhang, Wenfang
Abstract : This paper proposes a slotting construction strategy to avoid shear behavior of multistory masonry buildings. The aspect ratio of masonry piers increases via slotting between spandrels and piers, so that the limit state of piers under an earthquake may be altered from shear to rocking. Rocking piers with a structural concrete column (SCC) form a self-centering earthquake-resistant system. The in-plane lateral rocking behavior of masonry piers subjected to an axial force is predicted, and an experimental study is conducted on two full-scale masonry piers with an SCC, which consist of a slotting pier and an original pier. Meanwhile, a comparison of the rocking modes of masonry piers with an SCC and without an SCC was conducted in the paper. Experimental verification indicates that the slotting strategy achieves a change of failure modes from shear to rocking, and this resistant system with an SCC incorporates the self-centering and high energy dissipation properties. For the slotting pier, a lateral story drift ratio of 2.5% and a high displacement ductility of approximately 9.7 are obtained in the test, although the lateral strength decreased by 22.3% after slotting. The predicted lateral strength of the rocking pier with an SCC has a margin of error of 5.3%.